Formability characterization of steel tailor welded blanks formed through single point incremental forming - Usman Attique; Shahid Ikramullah Butt; Syed Hussain Imran Jaffery; Faping Zhang; Ghulam Hussain (Journal of Materials Research and Technology, 2024)
TWBs are being well formed by a simple, highly innovative method known as Incremental Sheet Forming (ISF). Both aluminum and steel sheets welded through friction stir welding (FSW), laser beam welding (LBW) or electron beam welding (EBW) have been explored, extensively, by researchers. However, no research is available on the formability characterization of selected steel sheets having thickness and strength differential, manually welded using Tungsten Inert Gas (TIG) welding technique and formed through Single Point Incremental Forming (SPIF). The same is addressed in this study. Variable wall angle truncated pyramid was used as test geometry. Tensile testing, microhardness and scanning electron microscope (SEM)/Energy Dispersive X-ray (EDX) analysis were performed before forming. Material selected for the study included deep drawing quality (DDQ) steel (DC06) and stainless steel (SS) (AISI 201). Because of huge difference in both strength and hardness values of DDQ steel and SS, low formability was achieved in case of strength differential with minimum and maximum forming depths of 1.8 mm and 3.6 mm, respectively. Whereas formability achieved in case of thickness differential was quite high with minimum and maximum values of forming depths of 27.8 mm and 36.6 mm, respectively since strength and hardness values were not varied much. Percentage thinning was used to assess formability achieved. Final thicknesses achieved during forming were verified by cosine law also. Research investigations may be applied in similar fashion for precise study of material characterization of various kinds of TWBs being used in multiple industries including automotive, vessel, medical, etc.